2018
DOI: 10.1371/journal.pone.0200426
|View full text |Cite
|
Sign up to set email alerts
|

Two-step production of anti-inflammatory soluble factor by Lactobacillus reuteri CRL 1098

Abstract: We have demonstrated previously that a soluble factor (LrS) produced by Lactobacillus (L.) reuteri CRL 1098 modulates the inflammatory response triggered by lipopolysaccharide. In this study, the production of LrS by L. reuteri CRL 1098 was realized through two steps: i) bacterial biomass production, ii) LrS production, where the bacterial biomass was able to live but did not proliferate. Therefore, the simultaneous evaluation of the effect of different factors on the growth and LrS production was performed. B… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 62 publications
0
4
0
Order By: Relevance
“…Of note, DSS-colitic mice treated with the probiotic showed a significant restoration of the mucosal epithelium, with restoration of mucin-producing goblet cells and lower inflammatory-cell infiltration in the lamina propria. Therefore, the administration of L. reuteri INIA P572 resulted in a significant reduction of the microscopic values compared to the DSS-colitic group, with a median (range) microscopic score of 14 (8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23).…”
Section: Intestinal Anti-inflammatory Effect Of L Reuteri Inia P572 In Experimental Colitismentioning
confidence: 90%
See 1 more Smart Citation
“…Of note, DSS-colitic mice treated with the probiotic showed a significant restoration of the mucosal epithelium, with restoration of mucin-producing goblet cells and lower inflammatory-cell infiltration in the lamina propria. Therefore, the administration of L. reuteri INIA P572 resulted in a significant reduction of the microscopic values compared to the DSS-colitic group, with a median (range) microscopic score of 14 (8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23).…”
Section: Intestinal Anti-inflammatory Effect Of L Reuteri Inia P572 In Experimental Colitismentioning
confidence: 90%
“…Some of the probiotic properties attributed to this species include the shortening of infant diarrheal events [9], the decrease in total and LDL-cholesterol levels in hypercholesterolemic subjects [10], the protection against Helicobacter pylori infection [11] or the reduction of intestinal inflammation in different experimental models of colitis in rodents [12][13][14][15][16][17]. Moreover, some of these probiotic properties are related to the capacity of certain L. reuteri strains to produce the antimicrobial compound reuterin during the anaerobic bioconversion of glycerol [8,18,19] or other metabolites with anti-inflammatory properties [17,20,21]. Recently, it was also demonstrated that reuterin from L. reuteri is a functional gut metabolite able to modulate Nutrients 2021, 13, 1860 2 of 18 host iron absorption by suppressing intestinal hypoxia-inducible factor 2α activity [22].…”
Section: Introductionmentioning
confidence: 99%
“…The components in LPW medium, sodium acetate, K2HPO4, ammonium citrate, MgSO4•7H2O and MnSO4•H2O were considered not to have a significant effect on the biomass production (Griet et al 2018) and based on the single variable experiments, polysorbate 80 doesn't induce a significant increase in the vitamin B12 production. Hence, in the present study, the effect of four factorspaneer whey (A), yeast extract (B), glycerol (C) and cobalt chloride (D) on the vitamin B12 production were optimized using Box Behnken design.…”
Section: Response Surface Methodologymentioning
confidence: 99%
“…19 Furthermore, several works demonstrated the capacity of LAB to modulate inflammation, and some strains may have a prophylactic and therapeutic effect in the prevention of IBD. 20,21 L. bulgaricus and L. fermentum inhibit the inflammation by decreasing the secretion of pro-inflammatory cytokines and preventing inflammatory response by suppressing the nuclear factor kappa light chain enhancer of NF-κB and p38 mitogen-activated protein kinase (MAPK) signaling pathways. 22…”
Section: Introductionmentioning
confidence: 99%